Kinematic parameters and oxygen uptake kinetics during sub-maximal exercise in swimming - Espada, Mário (2014)
Trabalho apresentado no 19 th Annual Congress of the European College of Sport Science, 2-5 julho 2014, Amesterdão, Holanda